Coated active material, positive electrode material, and battery
By covering a solid electrolyte layer with a specific composition on the surface of the positive electrode active material of the battery, the problem of increasing battery interface resistance is solved, and the battery charge and discharge efficiency and energy density is improved.
Patent Information
- Application Number
- CN202380051263.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-07
- Filing Date
- 2023-06-20
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing batteries, the transfer and receiving of lithium ions becomes easy at the interface of active substances coated by an electrolyte, but the transfer and receiving of electrons is limited, resulting in an increase in resistance and a decrease in characteristics of the interface.
By covering a first solid electrolyte layer with a thickness between 0 nm and 75 nm on the surface of the positive electrode active material, it includes Li, M1, O and X1, M1 is Ta or Nb, X1 is F, Cl, Br or I, Li/ The molar ratio of M1 is between 0.60 and 2.4, and the molar ratio of O/X1 is between 0.16 and 0.35.
The battery interface resistance is reduced, and the battery charge and discharge efficiency and energy density are improved.
Smart Images

Figure CN119487651A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a coated active material, a positive electrode material, and a battery. Background Art
[0002] Patent Document 1 discloses a battery using a positive electrode material in which at least a portion of the surface of a positive electrode active material is coated with an oxyhalide solid electrolyte.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2021 / 220924 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An object of the present disclosure is to provide a coated active material capable of reducing the interface resistance of a battery.
[0008] Means for solving problems
[0009] The coated active material disclosed in the present invention comprises an active material and a coating layer, wherein the coating layer contains a first solid electrolyte and covers at least a portion of the surface of the active material.
[0010] The first solid electrolyte comprises Li, M1, O and X1,
[0011] The above-mentioned M1 is at least one selected from Ta and Nb,
[0012] The above X1 is at least one selected from F, Cl, Br and I,
[0013] The thickness of the coating layer is greater than 0 nm and less than 75 nm.
[0014] The molar ratio Li / M1 of the Li and the M1 is 0.60 or more and 2.4 or less, and the molar ratio O / X1 of the O and the X1 is 0.16 or more and 0.35 or less.
[0015] Effects of the Invention
[0016] The present disclosure can reduce the interfacial resistance of a battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a cross-sectional view showing a schematic structure of the coated active material according to the first embodiment.
[0018] Figure 2 This is a cross-sectional view showing a schematic structure of a positive electrode material according to the second embodiment.
[0019] Figure 3 This is a cross-sectional view showing a schematic structure of a battery according to the third embodiment.
[0020] Figure 4 It is a graph showing an X-ray diffraction pattern of the first solid electrolyte.
[0021] Figure 5 This is the Nyquist plot of the battery of Example 1 at 3.85 V.
[0022] Figure 6 This is the Nyquist plot of the battery of Example 2 at 3.85 V.
[0023] Figure 7 This is the Nyquist plot of the battery of Example 3 at 3.85 V.
[0024] Figure 8 This is a Nyquist plot of the battery of Comparative Example 1 at 3.85 V. DETAILED DESCRIPTION
[0025] (Insights that form the basis of this disclosure)
[0026] Patent Document 1 states that the charge and discharge efficiency of a battery can be improved by using a positive electrode material in which at least a portion of the surface of a positive electrode active material is coated with an oxyhalide solid electrolyte.
[0027] Here, the inventors have found that at the interface of the active material covered by the electrolyte, the transfer of lithium ions becomes easy, but the transfer of electrons is rate-limited, resulting in an increase in the resistance of the interface and a decrease in the characteristics. In order to solve this problem, it is necessary to optimize the thickness of the coating.
[0028] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0029] (Implementation Method 1)
[0030] The coated active material of embodiment 1 comprises an active material and a coating layer, wherein the coating layer comprises a first solid electrolyte and covers at least a portion of the surface of the active material. The first solid electrolyte comprises Li, M1, O, and X1. M1 is at least one selected from Ta and Nb. X1 is at least one selected from F, Cl, Br, and I. The thickness of the coating layer is greater than 0 nm and is less than 75 nm.
[0031] Figure 1 1 is a cross-sectional view showing a schematic structure of the coated active material 130 according to Embodiment 1. The coated active material 130 according to Embodiment 1 includes an active material 110 and a coating layer 111. The active material 110 is in the shape of particles, for example. The coating layer 111 covers at least a portion of the surface of the active material 110.
[0032] The coating layer 111 is a layer containing a first solid electrolyte. The coating layer 111 is provided on the surface of the active material 110 .
[0033] By providing the coating layer 111, the transfer of lithium ions at the interface of the active material 110 becomes easy. In addition, by making the thickness of the coating layer 111 less than 75nm, the contact between the active materials 110 is improved, and the electronic resistance can be reduced. That is, since the thickness of the coating layer 111 is thin enough to ensure physical contact between the active materials 110 when the coated active materials 130 are pressed together, the coating layer 111 is flattened, thereby ensuring physical contact between the active materials 110, and thus the electronic resistance can be reduced. Therefore, the coated active material 130 of embodiment 1 can reduce the interface resistance of the battery.
[0034] The thickness of the coating layer 111 can be obtained, for example, by performing cross-section processing using an ion milling method and directly observing the cross-section using a scanning electron microscope (SEM). The thickness can be measured using a secondary electron image or a reflected electron image with an irradiation voltage of 1 kV and a magnification of 50,000 times. The thickness of a particle can be measured at any number of locations (e.g., 4 points), and this operation is performed on 10 particles, and the average value of the measured thickness is regarded as the thickness of the coating layer 111.
[0035] The coating layer 111 can uniformly coat the active material 110 .
[0036] The coating layer 111 may partially cover the surface of the active material 110. The particles of the active material 110 are in direct contact with each other via the portion not covered by the coating layer 111, thereby improving the electron conductivity between the particles of the active material 110. As a result, the battery can be operated at a high output.
[0037] The active material 110 and the coating layer 111 will be described in further detail.
[0038] (Coating layer 111)
[0039] The covering layer 111 covers at least a portion of the surface of the active material 110. The thickness of the covering layer 111 is greater than 0 nm and not more than 75 nm.
[0040] The thickness of the coating layer 111 may be 5 nm or more and 47 nm or less. According to the above description, the electronic resistance can be further reduced, and the interface resistance of the battery can be reduced.
[0041] The coating layer 111 includes a first solid electrolyte. The first solid electrolyte includes Li, M1, O, and X1. M1 is at least one selected from Ta and Nb. X1 is at least one selected from F, Cl, Br, and I.
[0042] The coating layer 111 may contain the first solid electrolyte as a main component, or may contain only the first solid electrolyte. "Main component" means the component that is contained most by mass ratio. The so-called "containing only the first solid electrolyte" means that no materials other than the first solid electrolyte are intentionally added except for inevitable impurities. For example, the raw materials of the first solid electrolyte, the by-products generated when the first solid electrolyte is made, etc. are contained in the inevitable impurities. The ratio of the mass of the inevitable impurities to the overall mass of the coating layer 111 can be less than 5%, less than 3%, less than 1%, or less than 0.5%.
[0043] In order to further improve the lithium ion conductivity, the first solid electrolyte may be substantially composed of Li, M1, O and X1. Here, "the first solid electrolyte is substantially composed of Li, M1, O and X1" means that the molar ratio of the total amount of the substance of Li, M1, O and X1 to the total amount of the substance of all elements constituting the first solid electrolyte is 90% or more. As an example, the molar ratio may be 95% or more.
[0044] In order to further improve lithium ion conductivity, the first solid electrolyte may include a crystal phase having a peak in a diffraction angle 2θ range of 11.05° to 13.86° in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu—Kα rays.
[0045] Here, the "peak" means a diffraction peak in an X-ray diffraction pattern.
[0046] The X-ray diffraction pattern of the first solid electrolyte of the first embodiment can be obtained by using Cu-Kα rays (wavelength and That is, wavelengths of 0.15405 nm and 0.15444 nm) and obtained by X-ray diffraction measurement using the θ-2θ method.
[0047] The molar ratio Li / M1 of Li and M1 is 0.60 to 2.4, and the molar ratio O / X1 of O and X1 is 0.16 to 0.35. Thus, lithium ion conductivity is improved.
[0048] The molar ratio Li / M1 was calculated using the formula: (amount of Li) / (total amount of Ta and Nb). The molar ratio O / X1 was calculated using the formula: (amount of O) / (total amount of F, Cl, Br and I).
[0049] In order to further improve the lithium ion conductivity, the molar ratio Li / M1 may be 0.96 or more and 1.20 or less.
[0050] X1 may be at least one selected from Cl, Br and I. X1 may also be Cl. The molar ratio O / Cl of O to Cl may be 0.16 or more and 0.35 or less. The molar ratio Li / M1 of Li to M1 may be 0.60 or more and 2.4 or less, and the molar ratio O / Cl of O to Cl may be 0.16 or more and 0.35 or less.
[0051] (Active substance 110)
[0052] The active material 110 may be a positive electrode active material.
[0053] The positive electrode active material includes a material having the characteristics of embedding and de-embedding metal ions (such as lithium ions). As the positive electrode active material, for example, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides and transition metal oxynitrides can be used. As examples of lithium-containing transition metal oxides, Li(NiCoAl)O2, Li(NiCoMn)O2 and LiCoO2 can be cited. In particular, when using lithium-containing transition metal oxides as the positive electrode active material, the manufacturing cost can be reduced and the average discharge voltage can be increased.
[0054] The positive electrode active material may be a composite oxide containing Ni and Co. The positive electrode active material having such a structure can improve the energy density and charge and discharge efficiency of the battery.
[0055] The active material 110 may include a reaction inhibiting layer formed of an oxide. The covering layer 111 may cover at least a portion of the surface of the active material 110 including the reaction inhibiting layer formed of an oxide.
[0056] The reaction inhibition layer may include a Li-Nb-O compound such as LiNbO3, a Li-BO compound such as LiBO2 and Li3BO3, a Li-Al-O compound such as LiAlO2, a Li-Si-O compound such as Li4SiO4, a Li-SO compound such as Li2SO4, or a Li4Ti5O 12 Li-Ti-O compounds, such as Li2ZrO3, such Li-Zr-O compounds, such Li2MoO3, such Li-VO compounds, such as LiV2O5, such Li-WO compounds, such as Li2WO4, or such Li-PO compounds as Li3PO4.
[0057] According to the above configuration, oxidation of the first solid electrolyte contained in the coating layer 111 can be suppressed.
[0058] <First solid electrolyte production method>
[0059] The first solid electrolyte included in the coating layer 111 can be produced by, for example, the following method.
[0060] Raw material powders are prepared and mixed so as to have a target composition. Examples of raw material powders are oxides, hydroxides, halides, or oxyhalides.
[0061] As an example, when the first solid electrolyte is composed of Li, Ta, O, and Cl, Li 2 O 2 and TaCl 5 are mixed at a molar ratio of Li 2 O 2 :TaCl 5 of 1:2 to prepare raw material powder.
[0062] The mixture of raw powders is allowed to react with each other mechanochemically in a mixing device such as a planetary ball mill to obtain a reaction product. This method is often referred to as mechanochemical grinding. The reaction product can be fired in a vacuum or in an inert atmosphere. Alternatively, the mixture can be fired in a vacuum or in an inert gas atmosphere to obtain a reaction product. Using these methods, the first solid electrolyte in the coated active material 130 of embodiment 1 can be obtained. The inert atmosphere is, for example, an argon atmosphere or a nitrogen atmosphere.
[0063] By selecting the raw material powder, the mixing ratio of the raw material powder, and the reaction conditions, the position of the peak of the first solid electrolyte in the coated active material 130 of the first embodiment, that is, the structure of the crystal phase can be adjusted to a target value.
[0064] The composition of the first solid electrolyte can be determined by, for example, inductively coupled plasma emission spectrometry or ion chromatography. For example, the compositions of Li and M1 can be determined by inductively coupled plasma emission spectrometry, and the composition of X1 can be determined by ion chromatography.
[0065] <Method for producing coated active material>
[0066] The coated active material 130 can be produced, for example, by the following method.
[0067] Prepare a powder of the active material 110 and a powder of the first solid electrolyte at a given mass ratio. For example, prepare a powder of Li(NiCoAl)O2 as the active material 110, and prepare a powder of LiTaOCl4 as the first solid electrolyte. Put these two materials into the same reaction container, and use rotating blades to apply shear force to the two materials. Alternatively, the two materials can be collided by using a jet of gas. By applying mechanical energy, the first solid electrolyte can be coated on at least a portion of the surface of the positive electrode active material.
[0068] The mixture of the active material 110 powder and the first solid electrolyte powder may be ground before mechanical energy is applied to the mixture. A mixing device such as a ball mill may be used for the grinding process. In order to suppress oxidation of the material, the grinding process may be performed in a dry atmosphere and an inert atmosphere.
[0069] The coated active material 130 can be manufactured by a dry particle composite method. The treatment by the dry particle composite method includes an operation of applying at least one mechanical energy selected from impact, compression and shear to the active material 110 and the first solid electrolyte. The active material 110 and the first solid electrolyte are mixed at an appropriate ratio.
[0070] The device used in the method for manufacturing the coated active material 130 is not particularly limited, and may be a device capable of imparting mechanical energy such as impact, compression, and shearing to the mixture of the active material 110 and the first solid electrolyte. As devices capable of imparting mechanical energy, there can be cited ball mills, jet mills, compression shearing processing devices (particle composite devices) such as "Mechanofusion" (manufactured by Hosokawa Micron) and "Nobilta" (manufactured by Hosokawa Micron), "Hybridization System (impact device in high-speed airflow)" (manufactured by Nara Machinery Manufacturing Co., Ltd.), and the like.
[0071] "Mechanofusion" is a particle compounding device that uses dry mechanical compounding technology by applying strong mechanical energy to multiple different raw material particles. In Mechanofusion, mechanical energy such as compression, shearing and friction is applied to the powder raw materials put between the rotating container and the pressure head, thereby compounding the particles.
[0072] "Nobilta" is a particle compounding device that uses dry mechanical compounding technology developed to compound nanoparticles as raw materials. Nobilta applies mechanical energy such as impact, compression, and shear to multiple raw material powders to produce composite particles.
[0073] In the case of "Nobilta", a rotor arranged in a horizontal cylindrical mixing container with a given gap between the rotor and the inner wall of the mixing container is rotated at high speed, and the raw material powder is repeatedly forced to pass through the gap. In this way, impact, compression and shear forces can be applied to the mixture to produce composite particles of the active material 110 and the first solid electrolyte. The conditions such as the rotor speed, processing time, and feed amount can be appropriately adjusted.
[0074] In the "Hybridization System", raw material powder is dispersed in a high-speed airflow while a force mainly composed of impact is applied, thereby producing composite particles of the active material 110 and the first solid electrolyte.
[0075] (Implementation Method 2)
[0076] Embodiment 2 will be described below. Explanations overlapping with those of Embodiment 1 described above will be appropriately omitted.
[0077] Figure 2 This is a cross-sectional view showing a schematic structure of a positive electrode material 1000 according to the second embodiment.
[0078] The positive electrode material 1000 of the second embodiment includes the coated active material 130 of the first embodiment and the second solid electrolyte 100. The second solid electrolyte 100 is in the form of particles, for example. The second solid electrolyte 100 can ensure sufficient ion conductivity of the positive electrode material 1000.
[0079] The active material 110 is separated from the second solid electrolyte 100 by the coating layer 111. The active material 110 may not be in direct contact with the second solid electrolyte 100. This is because the coating layer 111 has ion conductivity.
[0080] The coating layer 111 can uniformly coat the active material 110. The coating layer 111 inhibits direct contact between the active material 110 and the second solid electrolyte 100, thereby inhibiting side reactions of the second solid electrolyte 100. As a result, not only the charge and discharge efficiency of the battery is improved, but also the increase in the reaction overvoltage of the battery can be suppressed.
[0081] The second solid electrolyte 100 includes, for example, a material having high lithium ion conductivity. For example, the second solid electrolyte 100 has high lithium ion conductivity. Here, the high lithium ion conductivity is, for example, 1×10 -3 mS / cm or more. That is, the second solid electrolyte 100 contained in the positive electrode material 1000 of the second embodiment may have, for example, 1×10 -3 Ionic conductivity above mS / cm.
[0082] The second solid electrolyte 100 may be an oxyhalide solid electrolyte. By applying the technology disclosed in the present invention, a higher effect can be obtained.
[0083] The oxyhalide solid electrolyte may have the same composition as the first solid electrolyte of Embodiment 1. According to the above configuration, since the first solid electrolyte and the second solid electrolyte 100 are electrolyte materials having the same crystal phase, a good interface is formed between the first solid electrolyte and the second solid electrolyte 100. Thus, the charge and discharge efficiency of the battery can be improved.
[0084] The oxyhalide solid electrolyte may also have a composition different from that of the first solid electrolyte of Embodiment 1. That is, the second solid electrolyte 100 may also be an oxyhalide solid electrolyte having a composition different from that of the first solid electrolyte. As described above, the coating layer 111 inhibits direct contact between the active material 110 and the second solid electrolyte 100, thereby inhibiting the side reaction of the second solid electrolyte 100. According to the above configuration, since a material with higher lithium ion conductivity can be used as the second solid electrolyte 100, the characteristics of the battery can be improved. For example, the second solid electrolyte 100 may have higher lithium conductivity than the first solid electrolyte.
[0085] The oxyhalide solid electrolyte may include Li, M1, M2, O, and X2, wherein M2 is at least one selected from Zr, Y, La, and Al, and X2 is at least one selected from F, Cl, Br, and I.
[0086] In order to further improve the lithium ion conductivity, the second solid electrolyte 100 may be substantially formed of Li, M1, M2, O, and X2. Here, "the second solid electrolyte 100 is substantially formed of Li, M1, M2, O, and X2" means that the molar ratio of the total amount of the substances of Li, M1, M2, O, and X2 to the total amount of the substances of all elements constituting the second solid electrolyte 100 is 90% or more. As an example, the molar ratio may be 95% or more.
[0087] In order to further improve lithium ion conductivity, the second solid electrolyte 100 may be formed only of Li, M1, M2, O, and X2.
[0088] The oxyhalide solid electrolyte may contain a crystal phase having a peak in the range of diffraction angle 2θ of 11.08° or more and 15.63° or less in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays. That is, the second solid electrolyte 100 may contain a crystal phase having a peak in the range of diffraction angle 2θ of 11.08° or more and 15.63° or less in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays. The second solid electrolyte 100 having the above structure has high lithium ion conductivity because it is easy to form a path for lithium ion diffusion.
[0089] The X-ray diffraction pattern of the second solid electrolyte 100 can be obtained by using Cu-Kα rays (wavelength and That is, wavelengths of 0.15405 nm and 0.15444 nm) and obtained by X-ray diffraction measurement using the θ-2θ method.
[0090] X2 may be at least one selected from F, Cl and Br. X2 may be at least one selected from Cl and Br.
[0091] In the second solid electrolyte 100 , the molar ratio of M2 to the total of M1 and M2 may be greater than 0 and equal to or less than 0.60.
[0092] The molar ratio of M2 to the total of M1 and M2 is calculated using the mathematical formula: (amount of substance of M2) / (amount of substance of M1+amount of substance of M2). Hereinafter, the molar ratio of M2 to the total of M1 and M2 is also referred to as "M2 / (M1+M2) molar ratio".
[0093] In order to improve the electrochemical stability of the second solid electrolyte 100 , the molar ratio of F to X2 may be greater than or equal to 0 and less than or equal to 0.50.
[0094] The molar ratio of F to X2 is also referred to as “F / X2 molar ratio.” The molar ratio of F to X2 is calculated using the mathematical formula: (amount of substance of F) / (total amount of substance of F, Cl, Br, and I).
[0095] The shape of the second solid electrolyte 100 is not particularly limited. When the second solid electrolyte 100 is a powder, its shape may be, for example, needle-shaped, spherical, ellipsoidal, etc. For example, the second solid electrolyte 100 may be in the form of particles.
[0096] For example, when the second solid electrolyte 100 is in the shape of particles (e.g., spheres), the median particle size may be 100 μm or less. When the median particle size is 100 μm or less, the coated active material 130 and the second solid electrolyte 100 may form a good dispersion state in the positive electrode material 1000. Therefore, the charge and discharge characteristics of the battery are improved. In Embodiment 1, the median particle size of the second solid electrolyte 100 may be 10 μm or less.
[0097] According to the above configuration, in the positive electrode material 1000 , the coated active material 130 and the second solid electrolyte 100 can be well dispersed.
[0098] In the first embodiment, the median particle size of the second solid electrolyte 100 may be smaller than the median particle size of the coated active material 130 .
[0099] According to the above configuration, the second solid electrolyte 100 and the coated active material 130 can be in a more favorable dispersed state in the positive electrode material 1000 .
[0100] The median particle size of the coated active material 130 may be greater than or equal to 0.1 μm and less than or equal to 100 μm.
[0101] When the median particle size of the coated active material 130 is 0.1 μm or more, the coated active material 130 and the second solid electrolyte 100 can be well dispersed in the positive electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved.
[0102] When the median particle size of the coated active material 130 is 100 μm or less, the diffusion rate of lithium in the coated active material 130 is sufficiently ensured. Therefore, the battery can be operated at a high output.
[0103] The median particle size of the coated active material 130 may be larger than the median particle size of the second solid electrolyte 100. Thus, the coated active material 130 and the second solid electrolyte 100 may be in a well-dispersed state.
[0104] Here, the median diameter refers to the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, using a laser diffraction measuring device or an image analyzer.
[0105] In the positive electrode material 1000 of the second embodiment, the second solid electrolyte 100 and the coated active material 130 may be as follows: Figure 2 At this time, the coating layer 111 and the active material 110 are in contact with each other.
[0106] The positive electrode material 1000 of the second embodiment may include a plurality of particles of the second solid electrolyte 100 and a plurality of particles of the coated active material 130 .
[0107] In the positive electrode material 1000 of the second embodiment, the content of the second solid electrolyte 100 and the content of the coated active material 130 may be the same or different.
[0108] According to the above configuration, it is possible to suppress an increase in the internal resistance of the battery during charging.
[0109] The composition of the second solid electrolyte 100 can be determined by, for example, inductively coupled plasma emission spectrometry or ion chromatography. For example, the compositions of Li, M1, and M2 can be determined by inductively coupled plasma emission spectrometry, and the composition of X2 can be determined by ion chromatography.
[0110] <Method for producing positive electrode material>
[0111] By mixing the coated active material 130 with the second solid electrolyte 100, the positive electrode material 1000 can be obtained. The method of mixing the coated active material 130 with the second solid electrolyte 100 is not particularly limited. For example, the coated active material 130 and the second solid electrolyte 100 can be mixed using a mortar or other tool, or the coated active material 130 and the second solid electrolyte 100 can be mixed using a mixing device such as a ball mill. The mixing ratio of the coated active material 130 and the second solid electrolyte 100 is not particularly limited.
[0112] (Implementation 3)
[0113] Figure 3 This is a cross-sectional view showing a schematic structure of a battery 2000 according to the third embodiment.
[0114] The battery 2000 of the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The positive electrode 201 includes the positive electrode material in the second embodiment described above (for example, the positive electrode material 1000). The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203. With the above configuration, the initial efficiency of the battery 2000 can be improved.
[0115] Regarding the volume ratio "v1:100-v1" of the coated active material 130 and the second solid electrolyte 100 contained in the positive electrode 201, 30≤v1≤98 can be satisfied. Here, v1 represents the volume ratio of the coated active material 130 when the total volume of the coated active material 130 and the second solid electrolyte 100 contained in the positive electrode 201 is set to 100. When 30≤v1 is satisfied, sufficient battery energy density can be ensured. When v1≤98 is satisfied, it becomes easier for the battery 2000 to operate at high output.
[0116] The thickness of the positive electrode 201 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 is 10 μm or more, the energy density of the battery 2000 is sufficiently ensured. When the thickness of the positive electrode 201 is 500 μm or less, high-output operation can be achieved.
[0117] The electrolyte layer 202 is a layer containing an electrolyte. The electrolyte is, for example, a solid electrolyte. The solid electrolyte contained in the electrolyte layer 202 is called a third solid electrolyte. That is, the electrolyte layer 202 may contain a third solid electrolyte. The electrolyte layer 202 may also be a solid electrolyte layer.
[0118] The third solid electrolyte may be an oxyhalide solid electrolyte. A solid electrolyte having the same composition or the same crystal phase as the first solid electrolyte of Embodiment 1, or a solid electrolyte having the same composition or the same crystal phase as the second solid electrolyte 100 of Embodiment 2 may be used as the third solid electrolyte. That is, the electrolyte layer 202 may include a solid electrolyte having the same composition or the same crystal phase as the first solid electrolyte of Embodiment 1, or a solid electrolyte having the same composition or including the same crystal phase as the second solid electrolyte 100 of Embodiment 2.
[0119] In addition, the third solid electrolyte may be an oxyhalide solid electrolyte having a composition different from that of the first solid electrolyte, or an oxyhalide solid electrolyte having a composition different from that of the second solid electrolyte 100. That is, the electrolyte layer 202 may include an oxyhalide solid electrolyte having a composition different from that of the first solid electrolyte, or an oxyhalide solid electrolyte having a composition different from that of the second solid electrolyte 100 or having a different crystal phase.
[0120] The third solid electrolyte may be a halide solid electrolyte.
[0121] The difference between a halide solid electrolyte and an oxyhalide solid electrolyte lies in whether oxygen is intentionally contained.
[0122] When the third solid electrolyte is a halide solid electrolyte, Li3YX'6, Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4 and Li3(Al, Ga, In)X'6 etc. can be used as the halide solid electrolyte. Here, X' is at least one selected from Cl and Br.
[0123] The third solid electrolyte may be a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a complex hydride solid electrolyte.
[0124] When the third solid electrolyte is a sulfide solid electrolyte, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 As sulfide solid electrolytes, LiX, Li2O, MO can be added to them. q , Li p MO q The element X in "LiX" is at least one element selected from F, Cl, Br and I. q " and "Lip MO q The element M in "MO" is at least one element selected from P, Si, Ge, B, Al, Ga, In, Fe and Zn. q " and "Li p MO q " In this equation, p and q are independent natural numbers.
[0125] According to the above configuration, since the electrolyte layer 202 includes a sulfide solid electrolyte having excellent reduction stability, a negative electrode material having a low potential, such as graphite or metallic lithium, can be used, and the energy density of the battery 2000 can be increased.
[0126] When the third solid electrolyte is an oxide solid electrolyte, for example, NASICON-type solid electrolytes represented by LiTi2(PO4)3 and its elemental substitution products, (LaLi)TiO3-based perovskite-type solid electrolytes, and Li 14 ZnGe4O 16 , LISICON solid electrolytes represented by Li4SiO4, LiGeO4 and their elemental substitutes, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by and their elemental substitutions, Li3N and its H substitutions, Li3PO4 and its N substitutions, and glass or glass ceramics made of Li-BO compounds such as LiBO2 and Li3BO3 as basic materials and added with materials such as Li2SO4 and Li2CO3 as oxide solid electrolytes.
[0127] When the third solid electrolyte is a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used as the polymer solid electrolyte. The polymer compound can have an ethylene oxide structure. By having an ethylene oxide structure, the polymer compound can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) and LiC(SO2CF3)3 can be used as lithium salts. As a lithium salt, one lithium salt selected from the above can be used alone, or a mixture of two or more lithium salts selected from the above can be used.
[0128] When the third solid electrolyte is a complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used as the complex hydride solid electrolyte.
[0129] The electrolyte layer 202 may contain the third solid electrolyte as a main component. That is, the electrolyte layer 202 may contain, for example, 50% or more (ie, 50% by mass or more) of the third solid electrolyte in terms of mass ratio relative to the entire electrolyte layer 202 .
[0130] According to the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.
[0131] The electrolyte layer 202 may contain 70% or more (ie, 70% by mass or more) of the third solid electrolyte in terms of mass ratio relative to the entire electrolyte layer 202 .
[0132] According to the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.
[0133] The electrolyte layer 202 may contain the third solid electrolyte as a main component, and further contain inevitable impurities, or starting materials, by-products, and decomposition products used when synthesizing the third solid electrolyte.
[0134] For example, the electrolyte layer 202 may contain 100% (ie, 100% by mass) of the third solid electrolyte in terms of mass ratio relative to the entire electrolyte layer 202 excluding impurities inevitably mixed therein.
[0135] According to the above configuration, the charge and discharge characteristics of the battery 2000 can be further improved.
[0136] As described above, the electrolyte layer 202 may be composed of only the third solid electrolyte.
[0137] It should be noted that the electrolyte layer 202 may include two or more of the materials listed as the third solid electrolyte. For example, the electrolyte layer 202 may include a halide solid electrolyte and a sulfide solid electrolyte.
[0138] The thickness of the electrolyte layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 can be more reliably separated. When the thickness of the electrolyte layer 202 is 300 μm or less, high-output operation can be achieved.
[0139] The negative electrode 203 includes a material having the property of inserting and extracting metal ions (for example, lithium ions). The negative electrode 203 includes, for example, a negative electrode active material.
[0140] Metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used as negative electrode active materials. The metal material can be a single metal. Or the metal material can also be an alloy. Examples of metal materials include lithium metal and lithium alloys. Examples of carbon materials include natural graphite, coke, carbon in graphitization, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, or tin compounds can be used.
[0141] The negative electrode 203 may include a solid electrolyte material. As the solid electrolyte material, the solid electrolyte material exemplified as the material constituting the electrolyte layer 202 may be used. According to the above configuration, the lithium ion conductivity inside the negative electrode 203 can be improved, and high-output operation can be achieved.
[0142] The median particle size of the negative electrode active material particles can be greater than 0.1 μm and less than 100 μm. When the median particle size of the negative electrode active material particles is greater than 0.1 μm, the negative electrode active material particles and the solid electrolyte material can form a good dispersion state in the negative electrode. As a result, the charge and discharge characteristics of the battery are improved. In addition, when the median particle size of the negative electrode active material particles is less than 100 μm, the lithium diffusion in the negative electrode active material particles becomes faster. Therefore, the battery can operate at high output.
[0143] The median particle size of the negative electrode active material particles may be larger than the median particle size of the solid electrolyte material, thereby achieving a good dispersion state between the negative electrode active material particles and the solid electrolyte material.
[0144] The volume ratio "v2:100-v2" of the negative electrode active material particles and the solid electrolyte material contained in the negative electrode 203 can satisfy 30≤v2≤95. In the case of 30≤v2, sufficient battery energy density can be ensured. In addition, in the case of v2≤95, high output operation can be achieved.
[0145] The thickness of the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 203 is 10 μm or more, sufficient battery energy density can be ensured. When the thickness of the negative electrode 203 is 500 μm or less, high output operation can be achieved.
[0146] For the purpose of improving the adhesion of particles to each other, a binder may be included in at least one selected from the positive electrode 201, the electrolyte layer 202 and the negative electrode 203. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. In addition, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene can be used as a binder. Furthermore, two or more selected from the above substances may be mixed and used as a binder.
[0147] For the purpose of improving electron conductivity, at least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent. For example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene can be used as conductive auxiliary agents. When a carbon conductive auxiliary agent is used, low cost can be achieved.
[0148] It should be noted that the battery of the third embodiment can be configured as a battery in various shapes such as a coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, and laminated type.
[0149] (Other embodiments)
[0150] (Note)
[0151] The following techniques are disclosed through the description of the above embodiments.
[0152] (Technology 1)
[0153] A coated active material comprising an active material and a coating layer, wherein the coating layer comprises a first solid electrolyte and covers at least a portion of a surface of the active material.
[0154] The first solid electrolyte comprises Li, M1, O and X1,
[0155] The above-mentioned M1 is at least one selected from Ta and Nb,
[0156] The above X1 is at least one selected from F, Cl, Br and I,
[0157] The coating layer has a thickness greater than 0 nm and less than 75 nm, a molar ratio of Li to M1 (Li / M1) of 0.60 to 2.4, and a molar ratio of O to X1 (O / X1) of 0.16 to 0.35.
[0158] With this structure, the transfer of lithium ions at the interface of the active material becomes easy. In addition, by setting the thickness of the coating layer to 75nm, the contact between the active materials is improved, and the reduction of electronic resistance can be achieved. Therefore, the interface resistance of the battery can be reduced. In addition, with this structure, it is easy to form a crystal phase with high lithium ion conductivity in the first solid electrolyte, so the first solid electrolyte has a higher lithium ion conductivity. Therefore, the coated active material of technology 1 can improve the characteristics of the battery.
[0159] (Technique 2)
[0160] According to the coated active material described in technology 1, the thickness is greater than 5 nm and less than 47 nm. With this structure, the transfer of lithium ions at the interface of the active material becomes easy. In addition, by setting the thickness of the coating layer to greater than 5 nm and less than 47 nm, the contact between the active materials is improved, and the reduction of electronic resistance can be achieved. Therefore, the coated active material of technology 2 can reduce the interface resistance of the battery.
[0161] (Technique 3)
[0162] According to the coated active material described in technology 1 or 2, the first solid electrolyte contains a crystal phase having a peak in the range of diffraction angle 2θ of 11.05° or more and 13.86° or less in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays. With this configuration, it is easy to form a path for lithium ion diffusion in the first solid electrolyte, so the first solid electrolyte has high lithium ion conductivity. Therefore, the coated active material of technology 3 can improve the characteristics of the battery.
[0163] (Technique 4)
[0164] According to the coated active material described in technology 1, the molar ratio Li / M1 is greater than or equal to 0.96 and less than or equal to 1.20. With this configuration, it is easier to form a crystal phase with high lithium ion conductivity in the first solid electrolyte, so the first solid electrolyte has higher lithium ion conductivity. Therefore, the coated active material of technology 4 can improve the characteristics of the battery.
[0165] (Technique 5)
[0166] The coated active material according to any one of Techniques 1 to 4, wherein X1 is Cl. The coated active material of Technique 5 can improve battery characteristics.
[0167] (Technique 6)
[0168] The coated active material according to any one of techniques 1 to 5, wherein the active material is a positive electrode active material. With this configuration, the energy density and charge / discharge efficiency of the battery can be improved.
[0169] (Technique 7)
[0170] According to the coated active material described in the sixth aspect, the positive electrode active material is a composite oxide containing Ni and Co. With this configuration, the energy density and charge / discharge efficiency of the battery can be improved.
[0171] (Technology 8)
[0172] According to the coated active material described in Technology 6 or 7, the positive electrode active material has a reaction inhibition layer formed of an oxide. With this configuration, oxidation of the first solid electrolyte contained in the coating layer can be suppressed. Therefore, the coated active material of Technology 7 can improve the characteristics of the battery.
[0173] (Technique 9)
[0174] A positive electrode material comprising the coated active material described in any one of Techniques 6 to 8 and a second solid electrolyte.
[0175] With this configuration, the interface resistance of the battery can be reduced.
[0176] (Technology 10)
[0177] According to the positive electrode material described in the technique 9, the second solid electrolyte is a halogen oxide solid electrolyte. With this configuration, the charge and discharge efficiency of the battery can be improved.
[0178] (Technology 11)
[0179] According to the positive electrode material described in technology 10, the above-mentioned oxyhalide solid electrolyte has the same composition as the above-mentioned first solid electrolyte. With this composition, a good interface can be formed between the first solid electrolyte and the second solid electrolyte. Therefore, the charge and discharge efficiency of the battery can be improved.
[0180] (Technology 12)
[0181] According to the positive electrode material described in technology 10, the oxyhalide solid electrolyte has a composition different from that of the first solid electrolyte. According to this configuration, a material with higher lithium ion conductivity can be used as the second solid electrolyte. Therefore, the characteristics of the battery can be improved.
[0182] (Technology 13)
[0183] According to the positive electrode material described in any one of the techniques 10 to 12, the oxyhalide solid electrolyte comprises Li, M1, M2, O and X2, M2 is at least one selected from Zr, Y, La and Al, and X2 is at least one selected from F, Cl, Br and I. Since a path for lithium ion diffusion is easily formed in the second solid electrolyte, the second solid electrolyte has high lithium ion conductivity. Therefore, the characteristics of the battery can be improved.
[0184] (Technology 14)
[0185] The positive electrode material according to any one of techniques 10 to 13, wherein the oxyhalide solid electrolyte contains a crystal phase having a peak in the range of diffraction angle 2θ of 11.08° or more and 15.63° or less in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays. With this configuration, the second solid electrolyte has high lithium ion conductivity, thereby improving the characteristics of the battery.
[0186] (Technology 15)
[0187] According to the positive electrode material described in the technique 13, the above-mentioned X2 is at least one selected from Cl and Br. With this configuration, the ion conductivity of the second solid electrolyte can be increased, so the characteristics of the battery can be improved.
[0188] (Technology 16)
[0189] According to the positive electrode material described in technology 13 or 15, the molar ratio of the above-mentioned M2 to the sum of the above-mentioned M1 and the above-mentioned M2 is greater than 0 and is less than 0.60. With this configuration, the electrochemical stability of the second solid electrolyte can be improved, thereby improving the characteristics of the battery.
[0190] (Technology 17)
[0191] The positive electrode material according to any one of technologies 13, 15 and 16, wherein the molar ratio of F to the above X2 is 0 or more and 0.50 or less. With this configuration, the ion conductivity of the second solid electrolyte can be increased, thereby improving the characteristics of the battery.
[0192] (Technology 18)
[0193] A battery comprising:
[0194] A positive electrode comprising the positive electrode material described in any one of Techniques 9 to 17;
[0195] a negative electrode; and
[0196] An electrolyte layer is disposed between the positive electrode and the negative electrode.
[0197] By using the positive electrode material including the coated active material disclosed in the present invention as the positive electrode, the initial efficiency can be improved.
[0198] Example
[0199] Hereinafter, the details of the present disclosure will be described using Examples and Comparative Examples.
[0200] 《Example 1》
[0201] [Preparation of the First Solid Electrolyte and the Second Solid Electrolyte]
[0202] In an argon atmosphere with a dew point of less than -60°C, Li2O2 and TaCl5 as raw material powders were weighed so that the molar ratio of Li2O2:TaCl5=1:2. Thereafter, the obtained mixture was ground using a planetary ball mill (FRITSCH, P-7 type) for 12 hours at 600 rpm. Subsequently, the mixture was treated at 200°C for 3 hours to obtain powders of the first solid electrolyte and the second solid electrolyte of Example 1 formed of Li, Ta, O and Cl. That is, the first solid electrolyte and the second solid electrolyte are materials having the same composition as each other.
[0203] Since it was confirmed through preliminary experiments that the measured value of the composition of the obtained solid electrolyte is roughly the same as the feed ratio, the composition of the obtained solid electrolyte is expressed here as the feed ratio. The molar ratio of Li to Ta in the first solid electrolyte of Example 1 is Li / Ta is 1.0, and the molar ratio of O to Cl is O / Cl is 0.22.
[0204] The X-ray diffraction pattern of the first solid electrolyte of Example 1 was measured by the θ-2θ method using an X-ray diffractometer (Rigaku Corporation, MiniFlex600) in a dry environment with a dew point of -50°C or less. Cu-Kα radiation (wavelength and ) as the X-ray source. Figure 4 Graph showing an X-ray diffraction pattern of the first solid electrolyte. The first solid electrolyte has a peak in the range of diffraction angle 2θ of 11.05° or more and 13.86° or less. Since the second solid electrolyte is a material having the same composition produced by the same operation as the first solid electrolyte, it shows the same X-ray diffraction pattern.
[0205] [Preparation of coated active material]
[0206] In an argon atmosphere with a dew point of -60°C or less, Li(NiCoAl)O2 (hereinafter referred to as NCA) as a positive electrode active material and the first solid electrolyte of Example 1 were weighed in a manner such that the volume ratio was 100:1. These materials were placed in a dry particle composite device Nobilta (manufactured by Hosokawa Micron) and composited at 3000 rpm for 60 minutes to form a coating layer formed of the first solid electrolyte on the surface of the particles of the positive electrode active material. Thus, the coated active material of Example 1 was produced.
[0207] [Production of positive electrode materials]
[0208] In an argon atmosphere with a dew point of −60° C. or less, the coated active material of Example 1 and the second solid electrolyte were weighed so that the mass ratio was coated active material: second solid electrolyte = 77.68: 24.32. These materials were mixed in a mortar to prepare the positive electrode material of Example 1.
[0209] 《Example 2》
[0210] [Preparation of coated active material]
[0211] A coated active material of Example 2 was prepared in the same manner as in Example 1 except that the volume ratio of NCA to the first solid electrolyte was set to NCA:first solid electrolyte=100:5.
[0212] [Production of positive electrode materials]
[0213] In an argon atmosphere with a dew point of −60° C. or less, the coated active material of Example 2 and the second solid electrolyte were weighed so that the mass ratio was coated active material: second solid electrolyte = 78.12: 21.88. These materials were mixed in a mortar to prepare the positive electrode material of Example 2.
[0214] 《Example 3》
[0215] [Preparation of coated active material]
[0216] A coated active material of Example 3 was prepared in the same manner as in Example 1 except that the volume ratio of NCA to the first solid electrolyte was set to NCA:first solid electrolyte=100:10.
[0217] [Production of positive electrode materials]
[0218] In an argon atmosphere with a dew point of −60° C. or less, the coated active material of Example 3 and the second solid electrolyte were weighed so that the mass ratio was coated active material: second solid electrolyte = 81.45:18.55. These materials were mixed in a mortar to prepare the positive electrode material of Example 3.
[0219] Comparative Example 1
[0220] In Comparative Example 1, a coating layer of the positive electrode active material was not prepared. That is, NCA without a coating layer and the second solid electrolyte were weighed so that NCA: second solid electrolyte = 74.91: 25.09, and these materials were mixed in a mortar to obtain the positive electrode material of Comparative Example 1.
[0221] [SEM measurement of coating layer thickness profile]
[0222] Using the coated active materials of Examples 1 to 3 above, the thickness of the coating layer is measured. After the coated active material is mixed with the metal powder and granulated, a cross-section treatment is performed using ion milling. The thickness of the coating layer is measured at any multiple positions (4 points) of one particle using SEM. The measurement is performed on 10 particles, and the average value of the measured thickness is taken as the thickness of the coating layer. The thickness is measured based on a secondary electron image with an irradiation voltage of 1 kV and a magnification of 50,000 times.
[0223] [Battery production]
[0224] Using the positive electrode materials of Examples 1 to 3 and Comparative Example 1 described above, the following steps were carried out.
[0225] First, 60 mg of Li2S-P2S5, 20 mg of Li3Y1Br2Cl4, and the positive electrode material were stacked in order in an insulating outer cylinder. At this time, the mass of the positive electrode material was weighed so that the mass of the positive electrode active material was 10.35 mg. It was press-formed at a pressure of 720 MPa to obtain a positive electrode and a solid electrolyte layer.
[0226] Then, metal Li (thickness 200 μm) was stacked on the side of the solid electrolyte layer opposite to the side in contact with the positive electrode, and this was press-formed at a pressure of 80 MPa to produce a stacked body consisting of the positive electrode, the solid electrolyte layer, and the negative electrode.
[0227] Then, stainless steel current collectors were placed above and below the stacked body, and current collecting leads were attached to the current collectors.
[0228] Finally, an insulating hoop is used to isolate and seal the inside of the insulating outer cylinder from the outside atmosphere, thereby manufacturing a battery.
[0229] By means of the above operations, the batteries of Examples 1 to 3 and Comparative Example 1 were respectively manufactured.
[0230] [Charging test]
[0231] Using the batteries of Examples 1 to 3 and Comparative Example 1, a charging test was carried out under the following conditions.
[0232] The battery was placed in a constant temperature chamber at 25°C.
[0233] The battery was charged at a constant current of 80 μA to a voltage of 4.3 V and rested for 30 min at a current value of 0.05 C rate (20 hour rate) relative to the theoretical capacity of the battery. Thereafter, the battery was discharged at a constant current of 80 μA to a voltage of 2.5 V and rested for 30 min at a current value of 0.05 C rate (20 hour rate).
[0234] Then, the battery was measured by AC impedance method. The voltage amplitude was set to ±10 mV and the frequency was set to 10 7 to 10 -2 Hz. In addition, the electrochemical measurement system manufactured by Solartron was used for the measurement.
[0235] Figure 5 This is the Nyquist plot of the battery of Example 1 at 3.85 V. Figure 6 This is the Nyquist plot of the battery of Example 2 at 3.85 V. Figure 7 This is the Nyquist plot of the battery of Example 3 at 3.85 V. Figure 8 This is a Nyquist plot of the battery of Comparative Example 1 at 3.85 V. Figures 5 to 8 The horizontal axis and vertical axis represent the real part of the impedance and the imaginary part of the impedance, respectively. The waveform of the semicircular arc shown in the Nyquist plot is attributed to the resistance component with the positive electrode and the resistance component with the metal Li as the negative electrode, and a curve fitting analysis is performed to calculate the interface resistance value with the positive electrode for Examples 1 to 3 and Comparative Example 1, respectively.
[0236] Table 1 shows the ratio of the interface resistance values of Examples 1 to 3 when the interface resistance value of Comparative Example 1 is set to 100.
[0237] Table 1
[0238]
[0239] Investigation
[0240] According to the results of Examples 1 to 3 and Comparative Example 1 shown in Table 1, the resistance value reaches the minimum when the thickness of the coating layer is 12 nm, and the interface resistance gradually increases as the thickness increases. It is speculated that the coating can maintain the adhesion between the active material and the electrolyte and reduce the resistance to the insertion and extraction of Li. In addition, by thinly coating, the contact between the active materials and the active materials and the conductive additive is improved, and the interface resistance is reduced to 18.8% at most relative to Comparative Example 1.
[0241] Industrial Applicability
[0242] The battery disclosed herein can be utilized as, for example, an all-solid lithium secondary battery or the like.
[0243] Description of Reference Numerals
[0244] 130 coated active material, 1000 positive electrode material, 100 second solid electrolyte, 110 active material, 111 coating layer, 2000 battery, 201 positive electrode, 202 electrolyte layer, 203 negative electrode.
Claims
1. A coated active material comprising an active material and a coating layer, wherein the coating layer comprises a first solid electrolyte and covers at least a portion of a surface of the active material. The first solid electrolyte comprises Li, M1, O and X1, The M1 is at least one selected from Ta and Nb, X1 is at least one selected from F, Cl, Br and I, The thickness of the coating layer is greater than 0 nm and less than 75 nm, The molar ratio of Li to M1, Li / M1, is greater than or equal to 0.60 and less than or equal to 2.
4. The molar ratio O / X1 of the O and the X1 is 0.16 or more and 0.35 or less.
2. The coated active material according to claim 1, wherein The thickness is greater than or equal to 5 nm and less than or equal to 47 nm.
3. The coated active material according to claim 1, wherein The first solid electrolyte includes a crystal phase having a peak in a range of a diffraction angle 2θ of 11.05° to 13.86° in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu—Kα rays.
4. The coated active material according to claim 1, wherein The molar ratio Li / M1 is greater than or equal to 0.96 and less than or equal to 1.
20.
5. The coated active material according to claim 1, wherein The X1 is Cl.
6. The coated active material according to claim 1, wherein The active material is a positive electrode active material.
7. The coated active material according to claim 6, wherein The positive electrode active material is a composite oxide containing Ni and Co.
8. The coated active material according to claim 6, wherein The positive electrode active material includes a reaction inhibiting layer formed of an oxide. 9 . A positive electrode material comprising the coated active material according to claim 6 and a second solid electrolyte.
10. The positive electrode material according to claim 9, wherein The second solid electrolyte is an oxyhalide solid electrolyte.
11. The positive electrode material according to claim 10, wherein The oxyhalide solid electrolyte has the same composition as that of the first solid electrolyte.
12. The positive electrode material according to claim 10, wherein The oxyhalide solid electrolyte has a composition different from that of the first solid electrolyte.
13. The positive electrode material according to claim 10, wherein The oxyhalide solid electrolyte comprises Li, M1, M2, O and X2, M2 is at least one selected from Zr, Y, La and Al, X2 is at least one selected from F, Cl, Br and I.
14. The positive electrode material according to claim 13, wherein The oxyhalide solid electrolyte includes a crystal phase having a peak in a range of a diffraction angle 2θ of 11.08° or more and 15.63° or less in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu—Kα rays.
15. The positive electrode material according to claim 13, wherein The X2 is at least one selected from Cl and Br.
16. The positive electrode material according to claim 13, wherein The molar ratio of the M2 to the total of the M1 and the M2 is greater than 0 and is equal to or less than 0.
60.
17. The positive electrode material according to claim 13, wherein The molar ratio of F to the above X2 is 0 or more and 0.50 or less.
18. A battery comprising: A positive electrode comprising the positive electrode material according to any one of claims 9 to 17; negative electrode; and An electrolyte layer is disposed between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Positive electrode material, and battery
WO2021220924A1
Cited By
Composite polycrystalline positive electrode material, electrode plate and all-solid-state battery
CN120453350A